2020
DOI: 10.24016/2020.v6n3.173
|View full text |Cite
|
Sign up to set email alerts
|

Couple satisfaction and impact of confinement by COVID-19 pandemic in Mexico

Abstract: Background: The aim of the study was to evaluate the relationship between marital satisfaction, measured by the Relationship Assessment Scale, and the perceived impact of confinement due to COVID-19 in different areas of people’s lives, in a Mexican sample. Method: 101 people living as a couple, with an average age of 41.2 years (SD = 10.7), 54.5% women, and 45.5% of men were evaluated. Results: The main result was a negative and significant correlation that indicates that the greater the satisfaction in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
1
0
5
Order By: Relevance
“…As restrições atreladas ao confinamento foram consideradas custosas pelos participantes, por limitarem o lazer, a prática de atividades rotineiras em ambientes externos e a interação física com outros, assim como verificado em estudos internacionais (Quezada-Berumen et al, 2020;Randall et al, 2022;Weber et al, 2021). Tais medidas restritivas também reverberaram em dificuldades para os relacionamentos conjugais, principalmente no âmbito da sexualidade e dos conflitos, à medida que trouxe novos temas de conflito, como aqueles relacionados ao modo de enfrentar a pandemia, e intensificou problemas já existentes no relacionamento (Luetke et al, 2020;Salazar & Morales, 2020;Torres-Cruz et al, 2022).…”
Section: Considerações Finaisunclassified
See 2 more Smart Citations
“…As restrições atreladas ao confinamento foram consideradas custosas pelos participantes, por limitarem o lazer, a prática de atividades rotineiras em ambientes externos e a interação física com outros, assim como verificado em estudos internacionais (Quezada-Berumen et al, 2020;Randall et al, 2022;Weber et al, 2021). Tais medidas restritivas também reverberaram em dificuldades para os relacionamentos conjugais, principalmente no âmbito da sexualidade e dos conflitos, à medida que trouxe novos temas de conflito, como aqueles relacionados ao modo de enfrentar a pandemia, e intensificou problemas já existentes no relacionamento (Luetke et al, 2020;Salazar & Morales, 2020;Torres-Cruz et al, 2022).…”
Section: Considerações Finaisunclassified
“…Por outro lado, parceiros chineses que receberam apoio positivo durante o período mais crítico da pandemia sentiram mais gratidão e menos estresse (Jiang, Chiu, & Liu, 2022), e o apoio do parceiro se associou positivamente à satisfação conjugal em outros estudos (Enestrom & Lydon, 2021;Genç, Su, & Turhan, 2021). Casais mexicanos mais satisfeitos tenderam a experienciar menos impactos do confinamento no bem-estar geral e a acompanhar menos notícias relacionadas à covid-19 (Quezada-Berumen et al, 2020). O coping diádico também mediou a relação entre o estresse com a pandemia e a satisfação conjugal para homens e mulheres turcos (Genç et al, 2021), reduzindo o impacto negativo do sofrimento psicológico relacionado à pandemia na qualidade conjugal para a maioria dos participantes de um estudo multinacional .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…atât în cuplurile heterosexuale, cât şi în cele gay şi lesbiene . Satisfacţis maritală mai mare a fost legată de un impact mai scăzut al izolării asupra sănătăţii, a bunăstării fizice şi emoţionale (Quezada Berumen, Landero Hernández & González Ramírez, 2020).…”
Section: Relaţiile Romantice Ale Adulţilor îN Pandemieunclassified
“…Among couples with more positive functioning, satisfaction increased and maladaptive attributions decreased, while the opposite occurred among couples with lower functioning. Working along similar lines, Quezada et al (2020) assessed the relationship between the marital satisfaction of 101 Mexicans who were living with their partners and their experience of the lockdown. The study showed that those who were more satisfied with their relationships were more likely to have felt calm and happy during the lockdown and less likely to have suffered blows to their happiness, health, physical condition or emotional well-being.…”
Section: Introductionmentioning
confidence: 99%